2009
DOI: 10.3378/027.081.0407
|View full text |Cite
|
Sign up to set email alerts
|

Complete Mitochondrial Sequences for Haplogroups M23 and M46: Insights into the Asian Ancestry of the Malagasy Population

Abstract: Through the sequencing of the complete mitochondrial genome of three individuals of Malagasy ancestry, we completed the characterization of the island southeastern Asian specific M46 haplogroup. We assumed that the association of the np 3588 and np 16278 polymorphisms were M46 specific. In addition, we characterized a novel basal M subhaplogroup: M23. This clade can be defined by one coding region transition at np 10295 and one control region transition at np 16263. Our data suggest the arrival of South Asian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
3
5
0
Order By: Relevance
“…Subsequent research revealed the complex nature of settlement on this island, with the inclusion of at least three putative parental populations of African, Indonesian and Indian origin [4], [5], [6], [7]. A similar result was obtained for the Comoro Archipelago [8], [9].…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Subsequent research revealed the complex nature of settlement on this island, with the inclusion of at least three putative parental populations of African, Indonesian and Indian origin [4], [5], [6], [7]. A similar result was obtained for the Comoro Archipelago [8], [9].…”
Section: Introductionsupporting
confidence: 56%
“…The analysis of complete genome sequences from Madagascar revealed an autochthonous linage named M23 [4], [25]. Our complete mtDNA study also discovered an unidentified M type that only shares the common M mutations.…”
Section: Discussionmentioning
confidence: 59%
“…The isolate Ar2461 (Additional file 2: Table S1) has the diagnostic mutations of the Andaman branch M31a1 in the regulatory (249d, 16311) and coding (3975, 3999) regions. On the other hand, the complete mtDNA sequence of Ar1076 (Additional file 1: Figure S1) belongs to the M32c Andamanese branch, matching it with another complete sequence from Madagascar [72]. It must be stressed that this branch has been steadily found in all mtDNA reports on Madagascar [7375].…”
Section: Resultsmentioning
confidence: 90%
“…East Asian ancestry was assigned to haplogroups A12, B (excluding B2), C (excluding C1 and C4c), D (excluding D1 and D2a), E, F, M (excluding M1), N9, and Z. Although the origins of haplogroup M23 are still unclear [40,41] [43][44][45][46]. The Kimura 2-parameter model, which differentiates mutation rates of transitions from transversions, was used for Fst calculations [47], and Bonferroni corrections (simple and sequential) were applied before determining significant comparisons [48].…”
Section: Data Analysesmentioning
confidence: 99%